Analysis of Transport in Colombian Economy, Toughs and Challenges (2013)
Colombia government has led strong proposes to encourage rules for making public policies in transport sector. The idea is to achieve not only a way of improving the dynamic of sector but also find an analytic structure which allows keeping a steady- increase. This target is really important for the sector which has a significant relevance related to Colombian economy. Thus, the following essay looks for studying a public policy for the sector of transport. The structure of the paper begins with theory framework; secondly, it works with an analysis of the model for transportation; thirdly, public policies for transport sector and lastly its conclusion